Analisis Konsep Al-Ta’widh pada Ketentuan Ganti Rugi Pakaian Cucian yang Rusak di Jasa Laundry Syariah Arransha Kota Langsa - Indrayani, Dewi; Muttaqin, Zainal; Kurnia, Ryzka Dwi (IAIN Langsa, 2023)
This study aims to analyze the concept of al-ta'widh on the compensation provisions for damaged customer clothes in the Arransha Syariah Laundry service, Langsa City. The research method used is an empirical legal method that originates from primary and secondary qualitative data using descriptive analysis methods. The results of this study reveal: 1). The written compensation provisions applied to the Arransha Syariah Laundry service in Langsa City have not been detailed about the consequences of ignoring the second requirement, that is